Defect Investigation as a Tool for Quality Improvement - Gurumurthy, B.; Nagaraja, Y.N.; Nagesh, C.N.; Ravindra, G.S. (Defence Science Journal, 2002)
Defect investigation is an important tool for quality improvement as it identifies the root cause of errors and steps to be taken to eliminate these. In this paper, four cases of defect investigation are presented. The case studies cover link elevator, wing-fuselage attachment bolt, and stiff nut for Lakshya unmanned aerial vehicle. It was observed that the link elevator was discolourised even though the material used was the stainless steel. Investigations revealed that the stainless steel was heat-treated. In the case of leading edge, it was found that there was no provision for the location of a component in the tool, resulting in mismatch. Thread damage was noticed in wing-fuselage attachment bolts because of over tightening. All these studies resulted in improvement in the raw material bonding, inspection procedures, and fabrication methods, thus resulting in quality improvement.